The Effect of Company Size and Capital Structure on Financial Performance in Banking Companies Listed on the Indonesian Stock Exchange for the Period 2021–2024 - Muhammad Rizky Ramadhan; Marla Setiawati (Eduvest - Journal of Universal Studies, 2026)
This research aims to analyze the effect of firm size and capital structure on the financial performance of banking companies listed on the Indonesian Stock Exchange during the 2021–2024 period. Financial performance is proxied by Return on Assets (ROA), firm size is measured by total assets, and capital structure is measured using the Debt to Equity Ratio (DER). This research employs a quantitative approach with panel data regression analysis using secondary data obtained from annual financial reports. The model selection tests indicate that the Random Effect Model is the most appropriate. The results show that firm size has a positive and significant effect on financial performance, indicating that larger banks tend to achieve higher profitability due to better resource utilization and operational efficiency. Meanwhile, capital structure has a negative and significant effect on financial performance, suggesting that higher leverage increases financial risk and financing costs, which may reduce profitability. Simultaneously, firm size and capital structure significantly affect the financial performance of banking companies. These findings imply that banks should optimize asset management and maintain a balanced capital structure to improve profitability and ensure sustainable financial performance.